Effect of fractioning on antibacterial activity of n-butanol fraction from Enantia chlorantha stem bark methanol extract - Rebeca Madeleine Ebelle Etame; Raymond Simplice Mouokeu; Frank Stève Monthe Poundeu; Igor Kenfack Voukeng; Cedric Laurel Pouaha Cidjeu; Alembert Tchinda Tiabou; Abel Joel Gbaweng Yaya; Rosalie Anne Ngono Ngane; Jules Roger Kuiate; François Xavier Etoa (BMC, 2019)
Abstract Background Enantia chlorantha is a plant belonging to Annonaceae Family. The Barks and leaves are used traditionally to treat infectious diseases. Earlier studies highlighted the antibacterial activity of stem barks methanol extract. This study is thus aimed at investigating the effect of fractionation on antibacterial activity of its n-butanol fraction. Methods The extract of E. chlorantha stem barks was obtained by maceration in methanol and then subjected to a liquid/liquid partition by successive depletion with solvents of increasing polarity. The n-butanol fraction was fractionated by adsorption chromatography on silica gel. A product was isolated from the dichloromethane/methanol (2%) fraction and the structure was determined on the basis of spectroscopic data; Proton Nuclear Magnetic Resonance (1H NMR), Carbon-13 Nuclear Magnetic Resonance (13C NMR), Heteronuclear Multiple Bond Correlation (HMBC), H-correlation spectroscopy (H-COSY), attached proton test (APT), heteronuclear multiple quantum coherence (HSQC). The antibacterial activity was evaluated by broth microdilution method against six reference strains and eight clinical bacterial strains. Results The n-butanol fraction was found to be active with MIC values ranging from 32 to 256 μg/mL. The FA sub-fraction was more efficient among the eight sub-fractions, the n-butanol fraction and comparable to Chloramphenicol used as reference antibiotic. The product obtained was elucidated as palmitin. The antibacterial activity of the latter was comparable to that of Chloramphenicol on one reference strain and 4 of the 6 clinical strains. Conclusion The FA sub-fraction had better antibacterial activity than the n-butanol fraction and other sub-fractions, and possibly palmitin was the active substance responsible for the antibacterial activity of E. chlorantha.